Back injuries in Major League Baseball - Khachfe, H. H.; Fares, M. Y.; Salhab, H. A.; Fares, J. (The Journal of Sports Medicine and Physical Fitness, 2021)
BACKGROUND: There is a scarcity of epidemiological studies on back injuries in Major League Baseball (MLB). In our study, we explore all back related injuries in MLB from 2010 to 2016 (inclusive) with the aim to help better understand these injuries, assess their risks, and improve their prevention policies. METHODS: The transaction lists from the MLB website were screened for back injuries from 2010 through 2016. Only players who were placed on the disabled list (DL) for one or more days due to back-related injury were included in our study. Our database included the player`s position, team, injury location, injury type, days spent on the DL and month of injury occurrence. RESULTS: Two hundred fifty-four back injuries, an equivalent of 7% of all injuries, were recorded between 2010 and 2016 (inclusive). These injuries increased from 2010 to 2016. Back related injuries were found to place players on the disabled list for around 54 days. Injuries were recorded mostly during April, and strain was significantly greater than any other type of injury (P value <0.001). CONCLUSIONS: Back injuries are prevalent in the MLB. Better understanding of the trends and patterns of these injuries will help in establishing better prevention policies.